Flashcard-Based Think-Pair Share Cooperative Learning Model: Interest in Learning Aqidah and Morals - Suci Febhiyanti; Deden Makbuloh; M. Indra Saputra (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Learning interest is a crucial factor in the educational process because it plays a major role in student engagement in understanding the material. Based on the results of pre-research at MA Al Hikmah Bandar Lampung, it is known that student learning interest in the subject of Akidah Akhlak is still relatively low, especially in the aspects of attention and involvement, which is caused by the dominance of conventional methods and the lack of variety of learning media. This study aims to test the effectiveness of the cooperative learning model of the Think-Pair-Share (TPS) type assisted by flashcards media on increasing student learning interest. The approach used is quantitative with a quasi-experimental method of post-test only control group design. The research sample consisted of two classes, namely class X.A as the experimental group and class X.B as the control group. The data collection instrument used a non-test questionnaire that focused on indicators of attention in learning interest. The results of data analysis using the t-test showed a significance value of 0.001 (p < 0.05), which confirmed a significant difference in learning interest between the two groups. These findings prove that the combination of the TPS model and flashcards is effectively able to overcome the obstacles of low student attention and involvement. The synergy between independent thinking, pair discussions, and idea sharing, supported by visualization of material through flashcards, creates a more active and innovative learning environment. This study concludes that the flashcard-based TPS approach is an effective alternative learning strategy for increasing student motivation and interest in deepening the material on Aqidah and Akhlak.